Printable graphene inks with polypropylene carbonate for low-surface-tension solvents and mild-temperature post-processing - Huihui He; Jian Du; Jiaming Li; Yuxing Gu; Elad Koren; Woo Jin Hyun (Communications Materials)
Abstract For dispersion stability, printable graphene inks commonly employ solvents with limited surface tensions or incorporate dispersant aids that require high-temperature post-processing, restricting printability and substrate compatibility. Here, printable graphene inks are introduced with low-surface-tension solvents and mild-temperature post-processing using polypropylene carbonate (PPC). Graphene is produced by liquid-phase exfoliation with PPC, and the exfoliated graphene/PPC is used to generate printable inks. As a dispersant aid, PPC improves graphene exfoliation, dispersion stability, and redispersability in solvents with low surface tensions (<30 mJ m–2), facilitating the formulation of desirable inks for efficient aerosol jet printing on diverse substrates. Moreover, the low decomposition temperature of PPC eases its thermal removal from printed graphene, allowing high electrical conductivity with a mild post-processing temperature of 220 °C. Consequently, the graphene inks enable the fabrication of fully-printed graphene micro-supercapacitors on heat-sensitive paper substrates, exhibiting high areal capacitances, cycling stability, and mechanical resilience against bending deformation.